Evolutionary epidemiology of the monkeypox virus in Shandong Province during the post-global outbreak era - Li, Chengyunxiao; Xu, Dali; Duan, Qing; Wang, Hao; Li, Yan; Ding, Shujun; Liu, Ti; Li, Renpeng; Kou, Zengqiang; Yin, Chunhong (Frontiers in Microbiology, 2025)
IntroductionMonkeypox virus (MPXV) is an emerging zoonotic pathogen with increasing human-to-human transmission. Since the first case in Shandong Province in June 2023, 61 cases were reported by the end of 2024, predominantly among young men who have sex with men. Genomic and phenotypic characterization of circulating strains is crucial for assessing transmission dynamics and public health risks.MethodsGenomic sequencing was performed on the clinical samples to determine viral lineages and identify single nucleotide polymorphisms (SNPs). In vitro experiments were conducted to assess phenotypic differences among MPXV strains.ResultsSequencing revealed clustering into three main MPXV lineages C.1, C.1.1, and the emerging E.3, which became dominant in 2024. Molecular analyses identified 157 SNPs, most of which were APOBEC3-like mutations, suggesting host-driven viral editing. A higher number of SNPs and APOBEC3-related mutations in 2024 compared to 2023 indicates ongoing viral evolution. Phenotypic variability was observed among Clade IIb sub-lineages.DiscussionThese findings underscore the rapid diversification and adaptation of MPXV under sustained human-to-human transmission. They highlight the urgent need for integrated genomic and phenotypic surveillance to evaluate public health risks posed by emerging variants.